The effects of the Covid-19 pandemic on the management of learning and teaching in rural primary schools : the case of Kgakotlou Circuit, Limpopo Province - Mabapa, Grace Molepo (My University, 2024)
Despite various initiatives by the Department of Education in South Africa to support remote learning during the Covid-19 lockdown, rural primary schools faced significant challenges due to inadequate access to internet and other resources. The study was focused on exploring how the Covid-19 pandemic has affected the management of teaching and learning in selected rural primary schools at Kgakotlou Circuit, in the Limpopo Province. This study was informed by the theory of management as a guiding framework in this study. This study adopted a qualitative research approach and interview methods to explore the effect of Covid-19 pandemic on the management of teaching and learning in selected rural primary schools at Kgakotlou Circuit. Data were gathered from 13 key participants comprising of circuit manager, principals, departmental heads and educators from two rural primary schools. The findings from this research indicated that the national plans were put in place by the Department of Education to adapt with the new normal during the pandemic. The revised Annual Teaching Plans (ATPs) were also established to support the continuity of education during the crisis. Schools also promoted tailored online teaching and learning platforms besides giving learners daily homework and incorporating reading materials. However, lack of adequate resources, inequities in access to technology, lack of school-level planning, and untrained staff and other problems significantly affected the adoption and implementation of remote teaching and learning during the pandemic, especially in rural settings. Another finding suggests that the DBE supplied essential learning and teaching materials, such as revised Annual Teaching Plans (ATPs), Curriculum Assessment Policy Statements (CAPS) documents, learner books, teachers’ guides, DBE workbooks, and other supplementary materials. The rotation system was adopted by schools to accommodate learners while adhering to social distancing requirements, indicating a lack of infrastructural and staffing capacity to support daily attendance. The Annual Teaching Plans (ATPs) was also introduced to ensure continuity of education. However, various challenges faced by teachers during transitioning to virtual systems for training, workshops, and meetings. The key challenges included lack of understanding about the virtual system and the poor connectivity. This study recommends that rural schools should be prioritised in terms of resource allocation and capacity building.
Thesis (MPAM.) -- University of Limpopo, 2024
Keywords: COVID-19 pandemic; Department of Education; Management of learning and teaching; COVID-19 Pandemic, 2020-2023 -- Influence; School management and organization -- South Africa -- Limpopo; Curriculum-based assessment -- South Africa -- Limpopo; Education, Primary -- South Africa -- Limpopo